Bangtardi Design Using Macromedia Flash Flat Building Material to Increase Numeracy and Self Efficacy : Desain Bangtardi Melalui Macromedia Flash Materi Bangun Datar Untuk Meningkatkan Numerasi dan Self Efficacy - Zumrotun Nakidah; Mohamad Mohamad Fatih; Cindya Alfi (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Students' mathematical skills and autonomy in teaching and learning activities in the classroom are still low. It is important for teachers to pay attention to this problem so that students can adapt and have good job opportunities in their future lives. This study is a research and development (R&D) conducted using a waterfall development model consisting of five phases: requirements analysis and definition, system and software design, application and unit testing, system integration and testing, and operation and maintenance. Interview, survey and document instruments were used in conducting this study. Interviews were conducted in target schools for the purpose of observation, and surveys were conducted to determine the level of validity and adaptability of the media, as well as improving students' mathematical skills and independence. The results of the study showed that the Bangtardi environment based on Macromedia Flash is a valid environment according to the opinions of experts; 96.15% of media experts, 94.4% of language experts, and 92.5% of material experts agreed. Bangtardi media was also declared suitable for use in learning activities with a feasibility level of 100%. This environment has also proven to be effective in developing students' sense of responsibility and independence, with the results of the N-Gain value calculation being 0.7843, which shows that this environment is included in the very effective category.